Method for selectively enriching perovskite from titanium-containing blast furnace slag and synchronously preparing high-purity titanium dioxide

Through mechanical strengthening and reaction of nitric acid solution, combined with anionic surfactant and nitric acid steam, selective enrichment of perovskites and synchronous preparation of high-purity titanium dioxide are achieved, which solves the problem of low titanium resource recovery and achieves high efficiency and high purity titanium resources are utilized, reducing environmental pollution.

CN119194112APending Publication Date: 2024-12-27MEISHAN SHUNYING POWER BATTERY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411109003.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing technology cannot efficiently recycle and utilize titanium resources, resulting in accumulation of titanium-containing blast furnace slag, low environmental pollution and resource utilization.

Method used

After mechanical strengthening, react with nitric acid solution, combined with anionic surfactant and nitric acid steam, selective enrichment of perovskite and synchronous preparation of high-purity titanium dioxide are achieved, and the whole process is processed using normal pressure conditions.

Benefits of technology

It has achieved a utilization rate of more than 99% of titanium resources, a product purity of more than 99%, a short process flow, suitable for industrial applications, and reduced environmental pollution pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194112A_ABST
    Figure CN119194112A_ABST
Patent Text Reader

Abstract

The invention provides a method for selectively enriching perovskite from titanium-containing blast furnace slag and synchronously preparing high-purity titanium dioxide, and belongs to the field of comprehensive recycling of titanium-containing resources, and the method comprises the following steps: S1, carrying out mechanical strengthening on the titanium-containing blast furnace slag; s2, the strengthened blast furnace slag and water are mixed and stirred to be uniform, a nitric acid solution is added at the room temperature for a leaching reaction, and perovskite and leachate are obtained through solid-liquid separation; s3, nitric acid steam and an anionic surfactant are introduced into the obtained leachate, solid-liquid separation is performed after a heat preservation reaction, and porous silicon and liquid after silicon precipitation are obtained; s4, carrying out stirring reaction on the liquid subjected to silicon precipitation at 90-110 DEG C for 3-4 hours, carrying out solid-liquid separation to obtain a titanium dioxide precursor, and returning the obtained nitric acid steam to S3 for use; and S5, calcining the obtained precursor to obtain a high-purity titanium dioxide product. According to the method, titanium resources in the blast furnace slag are recycled step by step, one part is high-content perovskite, the other part is high-purity titanium dioxide, and maximum utilization of the titanium resources in the titanium-containing blast furnace slag is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of comprehensive recycling of titanium-containing resources, and specifically relates to a method for selectively enriching perovskite from titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide. Background Art

[0002] The blast furnace ironmaking process of vanadium-titanium magnetite will form titanium-containing blast furnace slag with complex mineral composition and structure, and titanium is distributed in multiple mineral phases. The existing process cannot further recover the titanium in it, nor can it be used by traditional smelting processes. It can only be stored in slag yards or prepared as construction aggregates.

[0003] Titanium-containing blast furnace slag is a valuable titanium resource, but due to the lack of efficient processing technology, a large amount of titanium-containing blast furnace slag has accumulated, which has brought great pressure to environmental pollution control. With the increasing shortage of titanium resources and the continuous increase in environmental protection efforts, the resource recycling of titanium-containing blast furnace slag has always been the focus of domestic research and exploration.

[0004] At present, the application of titanium extraction from titanium-containing blast furnace slag can be roughly divided into the following processes: (1) Acid method for preparing titanium dioxide, using inorganic acids such as hydrochloric acid / sulfuric acid to leach titanium, calcium, magnesium, aluminum and other elements, and then separating and purifying to obtain titanium dioxide. The titanium recovery rate of this method is 60~70%. At the same time, it is difficult to separate the impurity elements of calcium, magnesium and aluminum in the leachate, and the resource utilization rate is not high; (2) Alkaline method for preparing titanium dioxide, using alkaline substances to selectively extract titanium elements, and then preparing titanium dioxide products by adjusting the pH of the solution. This method consumes a lot of alkali. In addition, there are a large number of sodium ions in the leaching residue, which affects subsequent utilization; (3) High-temperature carbonization-low-temperature chlorination process, which converts titanium into titanium carbide, and then prepares it into titanium tetrachloride through a chlorination process to realize the utilization of titanium resources. This method has a titanium resource utilization rate of 70~80%, but it produces a large amount of chlorination waste residue, which is difficult to handle; (4) Selective enrichment-ore dressing separation process, which selectively enriches titanium in perovskite and then separates it through ore dressing methods to obtain titanium concentrate. The titanium concentrate obtained by this method has a low grade and a recovery rate of 40~50%, and the resource utilization rate is limited.

[0005] In summary, the current mainstream blast furnace slag titanium extraction processes all have problems such as low titanium resource utilization and poor product quality, which leads to the inability to large-scale industrial utilization of titanium-containing blast furnace slag. Therefore, it is of practical significance to develop a process technology route with high resource utilization, short process flow and excellent product quality. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides the following technical solutions:

[0007] A method for selectively enriching perovskite with titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide, the method comprising the following steps:

[0008] S1. Mechanically strengthen titanium-containing blast furnace slag;

[0009] S2, the strengthened blast furnace slag is mixed with water and stirred evenly, a nitric acid solution is added at room temperature to carry out a leaching reaction, and then the solid-liquid separation is carried out to obtain perovskite and a leachate;

[0010] S3, passing nitric acid vapor and anionic surfactant into the obtained leaching solution, and then separating the solid and liquid after heat preservation reaction to obtain porous silicon and silicon precipitation liquid;

[0011] S4, the liquid after silicon precipitation is stirred and reacted at 90-110°C for 3-4 hours, and the solid-liquid separation is performed to obtain a titanium dioxide precursor, and the obtained nitric acid vapor is returned to S3 for use;

[0012] S5. The obtained precursor is calcined to obtain a high-purity titanium dioxide product.

[0013] Preferably, in step S1, the mechanical strengthening is to subject the titanium-containing blast furnace slag to extrusion and grinding to expose a new surface, and the specific surface area of ​​the blast furnace slag after strengthening is 400-800m 2 / Kg. Controlling the specific surface area of ​​the strengthened blast furnace slag within the above range is a quantitative indicator for judging the mechanical strengthening effect. If the specific surface area is too low, the strengthening effect is poor, the leaching rate of elements such as silicon, titanium, calcium, magnesium, and aluminum is low, and a high content of perovskite phase cannot be effectively obtained; if the specific surface area is too high, the upper limit of mechanical strengthening has been reached, resulting in energy waste.

[0014] Preferably, in step S2, the mass ratio of the blast furnace slag to the mixing water is 2-3:1, and the reaction is stirred at room temperature for 15-30 minutes.

[0015] Preferably, in step S2, the mass concentration of nitric acid is 20-30%, the speed of adding nitric acid is 10-20 ml / min, the time of adding is controlled at 20-30 min, and the reaction temperature is controlled at 20-40 ° C. The reaction process mainly controls the speed and concentration of nitric acid addition. The reason is that the concentration of nitric acid is proportional to the oxidizability, and the reaction rate with the reducing substances in the blast furnace slag can be controlled by controlling the concentration of nitric acid. If the concentration of nitric acid is too high, the reaction system will be too violent and the reaction safety will be reduced. At the same time, high concentration of nitric acid and too fast addition speed will cause the local acidity and temperature of the leaching system to be too high, so that silicon is locally polymerized, thereby affecting the leaching of silicon. The main elements in the leachate are titanium (12-20 g / L), calcium (20-25 g / L), magnesium (8-10 g / L), aluminum (10-12 g / L), silicon (10-12 g / L), manganese (1-2 g / L), iron (0.5-1 g / L) and a small amount of sulfur (0.5 g / L).

[0016] Preferably, in step S2, the purity of the perovskite can reach above 94%.

[0017] Preferably, in step S3, the anionic surfactant is selected from at least one of sodium oleate, polyacrylamide, and sodium alkyl sulfonate. The purpose of adding the surfactant is to increase the polymerization rate of silicic acid, shorten the reaction time, and increase the filtration rate of the silicon precipitated material. The purpose of adding nitric acid vapor is to provide reaction heat while adding nitric acid, and the nitric acid vapor generated in the hydrolysis process of step S4 can be directly utilized.

[0018] Preferably, in step S3, after the nitric acid vapor is introduced into the leachate, the hydrogen ion concentration in the solution is 3-4 mol / L, the reaction temperature is increased to 50-65°C, and the reaction time is 3-4 hours. The above reaction conditions can polymerize the silicon in the leachate in the form of silicic acid, while titanium exists in the solution in the form of ions, thereby achieving the separation of titanium and silicon. The main components of the solution after silicon precipitation are titanium, calcium, magnesium, aluminum, and a small amount of manganese and iron. This part only precipitates and separates silicon, and the remaining ions (including titanium) exist in the solution in the form of ions.

[0019] Preferably, in step S3, the purity of the porous silicon is above 97%.

[0020] Preferably, in step S4, the TiO2 concentration in the post-siliconization liquid is 12-20 g / L, the reaction temperature is 90-110° C., and the reaction time is 3-4 h. The post-siliconization liquid is in a supersaturated state of TiO2 under heating conditions, so it can be separated. The steam generated by heating is a mixture of water and nitric acid, and the mass concentration of nitric acid in the reaction system is 20-30%. By using normal pressure evaporation, sufficient nitric acid can be added to step S3 to maintain the acidity required for the siliconization process.

[0021] Preferably, in step S5, the purity of the high-purity titanium dioxide is above 99%.

[0022] The present invention realizes efficient utilization of titanium resources in titanium-containing blast furnace slag and has the following advantages compared with the prior art:

[0023] 1) The present invention makes full use of the uneven state of titanium element in titanium-containing blast furnace slag to achieve the hierarchical utilization of titanium element. While preparing high-purity titanium dioxide, high-content perovskite is obtained, and the utilization rate of titanium resources can reach more than 99%.

[0024] 2) The whole process of the present invention is carried out under normal pressure, the reaction conditions are mild, the process flow is short, and it is easy to develop and use in industrialization.

[0025] In summary, the invention not only realizes the efficient recovery of titanium resources in titanium-containing blast furnace slag, but also opens up a new technical route for the comprehensive recovery and utilization of titanium-containing blast furnace slag, and has strong economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 The present invention provides a process flow chart for realizing the selective enrichment of perovskite from titanium-containing blast furnace slag and the simultaneous preparation of titanium dioxide.

[0028] Figure 2 This is the XRD analysis result of the perovskite prepared in Example 3 of the present invention.

[0029] Figure 3 This is the scanning electron microscope result of porous silicon prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0030] The following will describe the technical solutions and technical problems solved in the embodiments of the present invention in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0031] In the embodiments and comparative examples, the main element contents in the titanium-containing blast furnace slag are: Ti: 12.16%, Fe: 1.15%, Ca: 18.33%, Mg: 4.46%, Al: 7.63%, Mn: 0.58%, Si: 11.39%, S: 1.41%, and V: 0.12%.

[0032] Comparative Example 1

[0033] A method for selectively enriching perovskite with titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide, specifically comprising the following steps:

[0034] S1. Take titanium-containing blast furnace slag and put it into a dry ball mill for mechanical strengthening. After strengthening, the specific surface area of ​​the material is 200m 2 / Kg;

[0035] S2, take 100g of the blast furnace slag after strengthening and mix with 200ml of water and stir evenly, drip 600ml of nitric acid solution with a mass concentration of 30% at a speed of 30ml / min at 30°C, stir and react for 1h after the nitric acid is dripped, and then separate the solid and liquid to obtain perovskite and leachate, wherein the titanium content in the leachate is 7.5g / L, the silicon content is 10g / L, and the purity of the perovskite is only 80%. The leaching process did not meet expectations, and the next step of the experiment was not carried out. Comparative Example 1 Compared with the embodiment, the specific surface area of ​​the titanium-containing blast furnace slag in S1 after strengthening is too low, which makes it impossible to fully react with nitric acid, so the leaching does not meet expectations.

[0036] Comparative Example 2

[0037] A method for selectively enriching perovskite with titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide, specifically comprising the following steps:

[0038] S1. Take titanium-containing blast furnace slag and put it into a dry ball mill for mechanical strengthening. After strengthening, the specific surface area of ​​the material is 600m 2 / Kg;

[0039] S2, take 100g of blast furnace slag after strengthening and mix 200ml of water and stir evenly, drip 600ml of nitric acid solution with a mass concentration of 30% at a speed of 300ml / min at 30°C, stir and react for 1h after the nitric acid drips off, and then separate the solid and liquid to obtain perovskite and leachate, wherein the titanium content in the leachate is 5.4g / L, the silicon content is 0.23g / L, the perovskite purity is only 40.11%, and the solid-liquid separation is difficult, the leaching process does not meet expectations, and the next step of the experiment is not carried out. Comparative Example 2 Compared with the embodiment, the nitric acid is added too fast, resulting in too high acidity and temperature in the reaction process, and silicon is polymerized in advance, resulting in low perovskite purity.

[0040] Comparative Example 3

[0041] A method for selectively enriching perovskite with titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide, specifically comprising the following steps:

[0042] S1. Take titanium-containing blast furnace slag and put it into a dry ball mill for mechanical strengthening. After strengthening, the specific surface area of ​​the material is 600m 2 / Kg;

[0043] S2, take 100g of fortified blast furnace slag and mix with 200ml of water, stir evenly, add 600ml of 30% nitric acid solution at 30°C at a rate of 30ml / min, stir and react for 1h after the nitric acid is dripped, and then separate the solid and liquid to obtain perovskite and leachate, wherein the titanium content of the leachate is 12g / L, the silicon content is 10.5g / L, and the purity of the perovskite is 92.4%;

[0044] S3, take 300ml of the leaching solution obtained in S2, add 1ml of anionic surfactant solution with a mass concentration of 1% and polyacrylamide and sodium oleate as solutes (mass ratio 1:1), stir evenly, then introduce nitric acid vapor, so that the reaction system is heated to 75°C, the hydrogen ion concentration in the solution is 3.5mol / L, stir and react for 3h, then separate the solid and liquid to obtain silicon precipitation liquid and porous silicon, the titanium content in the silicon precipitation liquid is only 0.5g / L, and the experiment is terminated. Comparative Example 3 Compared with the embodiment, the temperature of the reaction system in step S3 is too high, resulting in titanium hydrolysis entering the solid phase together with the silicon slag, and the silicon and titanium separation cannot be achieved.

[0045] Comparative Example 4

[0046] A method for selectively enriching perovskite with titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide, specifically comprising the following steps:

[0047] S1. Take titanium-containing blast furnace slag and put it into a dry ball mill for mechanical strengthening. After strengthening, the specific surface area of ​​the material is 600m 2 / Kg;

[0048] S2, take 100g of fortified blast furnace slag and mix with 200ml of water, stir evenly, add 600ml of 30% nitric acid solution at 30°C at a rate of 30ml / min, stir and react for 1h after the nitric acid is dripped, and then separate the solid and liquid to obtain perovskite and leachate, wherein the titanium content in the leachate is 12g / L, the silicon content is 10.5g / L, and the purity of the perovskite is 94.27%;

[0049] S3, take 300ml of the leaching solution obtained in S2, add 1ml of anionic surfactant solution with a mass concentration of 1% and polyacrylamide and sodium oleate as solutes (mass ratio 1:1), stir evenly, then introduce nitric acid vapor, so that the reaction system is heated to 50°C, the hydrogen ion concentration in the solution is 1.5mol / L, stir and react for 3h, then separate the solid and liquid to obtain silicon precipitation liquid and porous silicon, the titanium content in the silicon precipitation liquid is only 3.5g / L, and the experiment is terminated. Comparative Example 4 Compared with the embodiment, the hydrogen ion concentration in the silicon precipitation process is too low, resulting in titanium entering the slag phase during the silicon polymerization process, and titanium silicon separation is not achieved.

[0050] Example 1

[0051] A method for selectively enriching perovskite with titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide, specifically comprising the following steps:

[0052] S1. Take titanium-containing blast furnace slag and put it into a dry ball mill for mechanical strengthening. After strengthening, the specific surface area of ​​the material is 600m 2 / Kg;

[0053] S2, take 100g of fortified blast furnace slag and mix with 200ml of water, stir evenly, add 600ml of 30% nitric acid solution at 30°C at a rate of 30ml / min, stir and react for 1h after the nitric acid is dripped, and then separate the solid and liquid to obtain perovskite and leachate, wherein the titanium content in the leachate is 12g / L, the silicon content is 10.5g / L, and the purity of the perovskite is 92.28%;

[0054] S3, take 300ml of the leaching solution obtained in S2, add 1ml of anionic surfactant solution with a mass concentration of 1% and polyacrylamide and sodium oleate as solutes (mass ratio 1:1), stir evenly, then introduce nitric acid vapor, so that the reaction system is heated to 55°C and the hydrogen ion concentration in the solution is 3.5mol / L, stir and react for 3h, then separate the solid and liquid to obtain silicon precipitation liquid and porous silicon, the titanium content in the silicon precipitation liquid is 12g / L;

[0055] S4, taking 200 ml of the silicon precipitate solution and stirring at 90-110°C for 3-4 hours, and then separating the solid and liquid to obtain 8.5 g of titanium dioxide precursor;

[0056] S5. Take 5 g of titanium dioxide precursor and calcine it at 900° C. for 2 h to obtain a high-purity titanium dioxide product. The purity of the product is measured to be 99%.

[0057] The applicant needs to explain that the titanium in blast furnace slag is mainly composed of two parts: one part is an uncrystallized glass phase and the other part is a perovskite phase. The perovskite contained in the blast furnace slag does not participate in the reaction under the conditions of the present invention and is enriched and purified, while other forms of titanium are leached into the solution. The titanium in the perovskite accounts for 30-35% of the total titanium in the blast furnace slag. Therefore, in the present invention, titanium is recovered in two forms, with a recovery rate of 30-35% in the form of perovskite, and the rest is recovered in the form of titanium dioxide.

[0058] In Example 1, the final perovskite yield was 11.5% (compared to blast furnace slag raw material), and the titanium recovery rate was 30.83%;

[0059] The porous silicon yield is 28% (compared to blast furnace slag raw materials), and the silicon recovery rate is 98.4%;

[0060] The main element contents in porous silicon are: Ti: 0.32%, Fe: 0.0021%, Ca: 0.02%, Mg: 0.005%, Al: 0.01%, Mn: 0.027%, S: 0.21%, and V: 0.0024%.

[0061] The main element contents in perovskite are: Ti: 32.6%, Ca: 27.5%, Fe: 0.3%, Mg: 0.5%, Al: 0.3%, Mn: 0.01%, Si: 1.20%, S: 0.5%, V: 0.21%.

[0062] The recovery rate of nitric acid during evaporation is 70%, and the rest is recovered in the nitrate system after hydrolysis.

[0063] Example 2

[0064] A method for selectively enriching perovskite with titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide, specifically comprising the following steps:

[0065] S1. Take titanium-containing blast furnace slag and put it into a dry ball mill for mechanical strengthening. After strengthening, the specific surface area of ​​the material is 800m 2 / Kg;

[0066] S2, take 100g of fortified blast furnace slag and mix with 200ml of water, stir evenly, add 600ml of 30% nitric acid solution at 30°C at a rate of 30ml / min, stir and react for 1h after the nitric acid is dripped, and then separate the solid and liquid to obtain perovskite and leachate, wherein the titanium content of the leachate is 12.5g / L, the silicon content is 11g / L, and the purity of the perovskite is 93.12%;

[0067] S3, take 300ml of the leaching solution obtained in S2, add 1ml of anionic surfactant solution with a mass concentration of 1% and polyacrylamide and sodium oleate as solutes (mass ratio 1:1), stir evenly, then introduce nitric acid vapor, so that the reaction system is heated to 55°C and the hydrogen ion concentration in the solution is 3.5mol / L, stir and react for 3h, then separate the solid and liquid to obtain silicon precipitation liquid and porous silicon, the titanium content in the silicon precipitation liquid is 10.6g / L;

[0068] S4, taking 200 ml of the liquid after silicon precipitation and stirring at 90-110°C for 3-4 hours, and then separating the solid and liquid to obtain 8.7 g of titanium dioxide precursor;

[0069] S5. Take 5 g of titanium dioxide precursor and calcine it at 900° C. for 2 h to obtain a high-purity titanium dioxide product. The purity of the product is measured to be 99.10%.

[0070] Example 3

[0071] A method for selectively enriching perovskite with titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide, specifically comprising the following steps:

[0072] S1. Take titanium-containing blast furnace slag and put it into a dry ball mill for mechanical strengthening. After strengthening, the specific surface area of ​​the material is 800m 2 / Kg;

[0073] S2, take 100g of fortified blast furnace slag and mix with 200ml of water, stir evenly, add 600ml of 30% nitric acid solution at 30°C at a rate of 30ml / min, stir and react for 1h after the nitric acid is dripped, and then separate the solid and liquid to obtain perovskite and leachate, wherein the titanium content of the leachate is 12.5g / L, the silicon content is 11g / L, and the purity of the perovskite is 93.12%; Figure 2 This is the XRD analysis result of the perovskite prepared in Example 3 of the present invention, indicating that the product is a pure phase.

[0074] S3, take 300ml of the leaching solution obtained in S2, add 1ml of anionic surfactant solution with a mass concentration of 1% and polyacrylamide and sodium oleate as solutes (mass ratio 1:1), stir evenly, then introduce nitric acid vapor, make the reaction system temperature rise to 60℃, the hydrogen ion concentration in the solution is 3.2mol / L, stir and react for 3h, then separate the solid and liquid to obtain silicon precipitation liquid and porous silicon, the titanium content in the silicon precipitation liquid is 10.6g / L; the electron microscope photo of porous silicon is as follows Figure 3 As shown, the purity of porous silicon is 97.50%.

[0075] S4, taking 200 ml of the liquid after silicon precipitation and stirring at 90-110°C for 3-4 hours, and then separating the solid and liquid to obtain 8.7 g of titanium dioxide precursor;

[0076] S5. Take 5 g of titanium dioxide precursor and calcine it at 900° C. for 2 h to obtain a high-purity titanium dioxide product. The purity of the product is measured to be 99.10%.

[0077] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for selectively enriching perovskite from titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide, characterized in that: The method comprises the following steps: S1. Mechanically strengthen titanium-containing blast furnace slag; S2, the strengthened blast furnace slag is mixed with water and stirred evenly, a nitric acid solution is added at room temperature to carry out a leaching reaction, and then the solid-liquid separation is carried out to obtain perovskite and a leachate; S3, passing nitric acid vapor and anionic surfactant into the obtained leaching solution, and then separating the solid and liquid after heat preservation reaction to obtain porous silicon and silicon precipitation liquid; S4, the liquid after silicon precipitation is stirred and reacted at 90-110°C for 3-4 hours, and the solid-liquid separation is performed to obtain a titanium dioxide precursor, and the obtained nitric acid vapor is returned to S3 for use; S5. The obtained precursor is calcined to obtain a high-purity titanium dioxide product.

2. The method for selectively enriching perovskite from titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide according to claim 1, characterized in that: In step S1, the mechanical strengthening is to subject the titanium-containing blast furnace slag to extrusion and grinding to expose a new surface, and the specific surface area of ​​the blast furnace slag after strengthening is 400-800m 2 / Kg.

3. The method for selectively enriching perovskite from titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide according to claim 1, characterized in that: In step S2, the mass ratio of the blast furnace slag to the mixing water is 2-3:1, and the reaction is stirred at room temperature for 15-30 minutes.

4. The method for selectively enriching perovskite from titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide according to claim 1, characterized in that: In step S2, the mass concentration of nitric acid is 20-30%, the speed of adding nitric acid is 10-20 ml / min, the time of adding is controlled at 20-30 min, and the reaction temperature is controlled at 20-40° C.

5. The method for selectively enriching perovskite from titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide according to claim 1, characterized in that: In step S2, the purity of the perovskite is above 94%.

6. The method for selectively enriching perovskite from titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide according to claim 1, characterized in that: In step S3, the anionic surfactant is selected from at least one of sodium oleate, polyacrylamide, and sodium alkyl sulfonate.

7. The method for selectively enriching perovskite from titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide according to claim 1, characterized in that: In step S3, after the nitric acid vapor is introduced into the leachate, the hydrogen ion concentration in the solution is 3-4 mol / L, the reaction temperature is increased to 50-65° C., and the reaction time is 3-4 h.

8. The method for selectively enriching perovskite from titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide according to claim 1, characterized in that: In step S4, the TiO2 concentration in the silicon precipitation solution is 12-20 g / L, the reaction temperature is 90-110°C, and the reaction time is 3-4 h.

9. The method for selectively enriching perovskite from titanium-containing blast furnace slag and simultaneously preparing high-purity titanium dioxide according to claim 1, characterized in that: In step S5, the purity of the high-purity titanium dioxide is above 99%.